Application of Artificial Intelligence in Applied Biology and Health Sciences - Kurian, Binoy (Asian Journal of Engineering and Applied Technology, 2022)
In modern world, artificial intelligence will substitute or magnify human competency in Applied Biology and Health Sciences. AI is the cognitive brilliance manifested by machines or software. AI is growing as an outstanding field in information technology as it enriched the mankind in many circumstances. The application of AI across different disciplines promises an alternative sustainable solution for all human problems. AI is developed in last 10 years as a life changer; when it stated solving human problems easily. This includes solving protein architecture, drug discovery and design, drug recycling, drug safety, diagnose patients, to choose a suitable crop, to determine when to fertilize crops, to avoid adulteration of seeds, to diagnose the crop infections, for proper application of pesticides and herbicides, to identify and removal of weeds, to identify natural ripening of fruits, for the detection of food nutrient value, agri-products for the health and weather forecasting.